About feminicide, the woman’s right to name her experiences - Romio, Jackeline Aparecida Ferreira (Plural, 2019)
The article argues the need to analyze the violence and death of women looking for understand it within the complex framework of the policies of control the body and sexuality of woman. This approach has been especially produced by feminists through the characterization of the phenomenon called feminicide. The article analyzes and explains how the concept of feminicide has been modernized and amplified in the conceptual field and adjusted to Latin American national realities and law.